Development of an Electronic Dictionary of Monocotyledon Plant Classification for Jambi University Biology Education Students - Muswita; Upik Yelianti; M. Erick Sanjaya; Ali Sadikin; Asni Johari (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to develop an Electronic Dictionary of Monocotyledon Plant Classification for Biology Education students at Jambi University. The primary issue faced by students is the lack of interactive learning media to facilitate their understanding of monocotyledon plant classification. To address this issue, the Research and Development (R&D) method was used, applying the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). In the needs analysis stage, observations and interviews were conducted to identify gaps in traditional learning materials. In the design stage, the e-dictionary was developed using Macromedia Flash 8 Pro, focusing on presenting taxonomic descriptions and interactive visual elements. Validation was carried out by content and media experts, resulting in improved scores from 75% to 89.06% for content experts, and from 62.50% to 87.50% for media experts. In the implementation stage, the e-dictionary was tested on 40 students, yielding a satisfaction score of 83.34%, with an independent evaluation from lecturers scoring 93.75%. The study demonstrates that the e-dictionary is effective in enhancing students' understanding of monocotyledon classification. Recommendations for future research include developing Augmented Reality (AR) features and adapting the tool for other biology education content. This e-dictionary is expected to contribute to more interactive and flexible biology learning.